L’evoluzione del Catasto nella mostra "Un tesoro ritrovato. Dal rilievo alla rappresentazione” - Redazione, Redazione (GEOmedia, 2009)
The evolution of cadastre between tradition and future applications The evolution of cadastre during the last three centuries has been the main focus of an exhibition held in Rome, since the 26th of november 2009 until the last 10th of january. The event has been organized by the italian Cadastral Agency (formerly Agenzia del Territorio) and it featured maps, instruments and experiences collected during the last three centuries. The awareness of the technological advancements of the instruments for surveying, acquisition, management and representation of land data could be very useful in order to understand the importance of cadastre in the control and management of our land.